2017
DOI: 10.1515/raon-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors affecting intraoperative 5-aminolevulinic acid-induced fluorescence of diffuse gliomas

Abstract: BackgroundIn patients operated for malignant glioma, 5-aminolevulinic acid (5-ALA)-induced fluorescence guidance is useful. However, we occasionally experience instances of non-visible fluorescence despite a histopathological diagnosis of high-grade glioma. We sought to identify factors that influence the intraoperative visualization of gliomas by their 5-ALA-induced fluorescence.Patients and methodsWe reviewed data from 60 patients with astrocytic or oligodendroglial tumors who underwent tumor removal under 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…As the vast majority of glioblastomas shows strong PpIX‐fluorescence, a dependence on MGMT‐status as a determining single factor can be excluded. While an in vitro study found stronger PpIX fluorescence in cells harboring IDH‐1 mutation, clinical experience seems to point in the opposite direction, finding non‐fluorescent gliomas predominantly in the IDH mutated subgroup . It may be worth mentioning that the rate of contrast enhancement in MRI among the IDH mutant gliomas is also lower than with IDH wild‐type ones , suggesting that this effect may be caused by differences in BBB deficiency.…”
Section: ‐Ala—fundamentalsmentioning
confidence: 97%
“…As the vast majority of glioblastomas shows strong PpIX‐fluorescence, a dependence on MGMT‐status as a determining single factor can be excluded. While an in vitro study found stronger PpIX fluorescence in cells harboring IDH‐1 mutation, clinical experience seems to point in the opposite direction, finding non‐fluorescent gliomas predominantly in the IDH mutated subgroup . It may be worth mentioning that the rate of contrast enhancement in MRI among the IDH mutant gliomas is also lower than with IDH wild‐type ones , suggesting that this effect may be caused by differences in BBB deficiency.…”
Section: ‐Ala—fundamentalsmentioning
confidence: 97%
“…Analysis was as previously described. 15 TERT mutations were confirmed by direct sequencing. A fragment of the TERT promoter was amplified with a primer (5′-GTCCTGCCCCTTCACCTT-3′ [forward], 5′-GCACCTCGCGGTAGTGG-3′ [reverse]) that contained the C228T and C250T mutation sites.…”
Section: Analysis Of Idh1 and Tert Mutationsmentioning
confidence: 99%
“…Stummer et al . 8 reported that progression-free survival (PFS) was prolonged when ALA-PDD was used during glioblastoma surgery, and 5-ALA has already been approved as a diagnostic drug for grade III and IV glioma in Europe, Japan and the USA 9,10 . Recently, 5-ALA was also approved as a diagnostic agent for nonmuscle invasive bladder cancer in Japan 11 .…”
Section: Introductionmentioning
confidence: 99%